The impacts of COVID-19 on female labor force participation in Iran - Hai-Anh H. Dang; Djavad Salehi-Isfahani; Minh N. N. Do (Global Labor Organization (GLO), 2024)
While female labor force participation (LFP) in Iran is among the lowest in the world, there is hardly any study on the COVID-19 pandemic effects on the country's female LFP. We find that female LFP decreased during the pandemic years by around 1 percentage point in 2021 and 2022. When controlling for excess mortality rates, the declines could increase to between 3.9 and 8.7 percentage points, with the larger impacts occurring in late 2021 and early 2022. Compared to modest, pre-pandemic female LFP rates, these figures translate into 5 percent and 18-40 percent decreases, respectively. Heterogeneity exists, with more educated individuals being more likely to work. Compared to married individuals, divorcees were more likely to work while those that were divorced or never married were less likely to work. Our results offer relevant inputs for labor policy, particularly those aimed at reducing gender inequalities.
Keywords: E24; I30; J21; O12; 330; COVID-19; employment; women's labor force participation; differences-in-differences; triple differences; labor force survey; Iran